THAILAND AND MALAYSIA’S COMPETITIVENESS ON ELECTRIC VEHICLE MANUFACTURING DEVELOPMENT TO INCREASE THE FOREIGN DIRECT INVESTMENT IN 2014-2019 - Anggara Raharyo; Saffira Dellavia (President University, 2023)
The Electric Vehicle (EV) development become one of the factor for Thailand and Malaysia to create a policy for accelerate electric vehicle development due their interest to develop the electric vehicle sector in their country. This interest led to the competitiveness between those countries. In order to help them developing their electric vehicle sector, Thailand and Malaysia need to allow foreign direct investment to their country to help them gain advance technology to develop their electric vehicle sector. The competitiveness that occurs between Thailand and Malaysia can be analyzed through Porter Diamond Model to understand the advantage from each country that can attract the foreign direct investment to their country. Thailand shows the competitiveness in EV more than Malaysia because in those several determinants, Thailand shows they keep developing through their policies, providing infrastructure, and continuing the research and development in production capability. Although Malaysia has several advantages than Thailand, but Thailand could provide more benefits to the investor than Malaysia.